2019
DOI: 10.1108/ijppm-03-2019-0127
|View full text |Cite
|
Sign up to set email alerts
|

Client protection and sustainable performance in microfinance institution

Abstract: Purpose Microfinance institutions (MFIs) provide credit to low-income beneficiaries, enabling them to gain access to financial assistance. To ensure that clients are protected, all MFIs should adhere to basic corporate governance principles to guarantee uniform standards, transparency and good corporate governance practices in their institutions. Hence, the purpose of this paper is to explore the client protection practices and sustainable performance of Amanah Ikhtiar Malaysia (AIM), a leading MFI in Malaysia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…IMFI's and community welfare through increased outreach to the poor. Bakar et al. (2019) , making Amanah Ikhtiar Malaysia (AIM) as the object of research proves that the accountability and collection process by IMFI positively impacts sustainability.…”
Section: Existing Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…IMFI's and community welfare through increased outreach to the poor. Bakar et al. (2019) , making Amanah Ikhtiar Malaysia (AIM) as the object of research proves that the accountability and collection process by IMFI positively impacts sustainability.…”
Section: Existing Researchmentioning
confidence: 99%
“…The correct application of the Shariah contract has proven to make IMFI more sustainable ( Aliyu et al., 2017 ). In addition, accountability and collection processes affect the sustainability of IMFI's ( Bakar et al., 2019 ). However, the source of funds also affects the sustainability of IMFI's ( Said et al., 2019 ; Sukmana et al., 2020 ).…”
Section: Existing Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Effective management in microfinance entails not only financial controls and operational efficiency but also a profound grasp of clients’ socio-economic contexts. Balancing the dual goals of serving the underserved while ensuring financial sustainability through appropriate interest rates, loan repayment, and operational efficiency is paramount [ 14 , 57 , 58 ].…”
Section: Network Analysis and Microfinance Topicsmentioning
confidence: 99%
“…However, the cost of microcredit remains a drawback, constraining the performance of MSEs in Ghana. Besides this, those institutions working on client protection where, (Bakar, et. al, 2020) showed that the level of client protection in (Amanah Ikhtiar Malaysia) AIM is high.…”
Section: Institutional Perspectivementioning
confidence: 99%